Prevalence of Anxiety and Depression in Patients with dissociative disorders - Siddique, Irum; Dogar, Imtiaz Ahmad; Haider, Nighat; Afzal, Samreen (Journal of Pakistan Psychiatric Society, 2015)
Abstract